Overall survival and final efficacy and safety results from a Japanese phase II study of axitinib in cytokine‐refractory metastatic renal cell carcinoma. Issue 12 (25th November 2014) - Eto, Masatoshi; Uemura, Hirotsugu; Tomita, Yoshihiko; Kanayama, Hiroomi; Shinohara, Nobuo; Kamei, Yoichi; Fujii, Yosuke; Umeyama, Yoshiko; Ozono, Seiichiro; Naito, Seiji; Akaza, Hideyuki; the Japan Axitinib Phase II Study Group
<x xml:space="preserve">Abstract</x> In an open‐label, multicenter phase II study of Japanese patients with cytokine‐refractory metastatic renal cell carcinoma, axitinib showed substantial antitumor activity with an acceptable safety profile. Here, we report overall survival and updated efficacy and safety results. Sixty‐four Japanese patients with metastatic renal cell carcinoma following prior therapy with cytokines were treated with axitinib at a starting dose of 5 mg b.i.d. Following median treatment duration of 14.2 months, median overall survival was 37.3 months (95% CI, 28.6–49.9). The objective response rate, the primary endpoint of the study, was 51.6% (95% CI, 38.7–64.2); the median duration of response, 11.1 months (95% CI, 8.2–13.7); and the median progression‐free survival was 11.0 months (95% CI, 9.2–12.0), assessed by the independent review committee. Common treatment‐related all‐grade adverse events were hypertension (88%), hand‐foot syndrome (75%), diarrhea (66%), proteinuria (63%), fatigue (55%) and dysphonia (53%). In an exploratory analysis, median overall survival was found to be significantly longer in patients who had greater decreases in plasma levels of soluble vascular endothelial growth factor receptor‐2 during the first cycle of treatment. In conclusion, the present study showed axitinib to be effective, and toxicities with long‐term treatment were generally controllable with axitinib dose modification and/or standard medications in these Japanese patients. Some frequently reported adverse events warrant close monitoring and management. Changes in the plasma levels of soluble vascular endothelial growth factor receptor‐2 may be used as a prognostic factor for overall survival in metastatic renal cell carcinoma following axitinib treatment. This study is registered at ClinicalTrial.gov (identifier NCT00569946).